Recycled aluminium cooking pots: a growing public health concern in poorly resourced countries - Angela Mathee; Renée Street (BMC, 2020)
Abstract Lead exposure remains a significant public health problem, particularly in the informal sector. Recycling of scrap metal into artisanal pots is a growing concern in poorly resourced countries. Owing to the relatively light weight and low cost of the artisanal pots, as well as good conductivity which equates to lower usage of wood fuel, the pots are widely used. The aim of this article is to describe current insights and emerging evidence of health risks associated with artisanal pot making and usage. This thriving industry, particularly in poorly resourced communities, has multifaceted occupational, environmental and human health impacts. Given the complexity, innovative solutions need to be prioritized, evaluated and scaled up in relevant settings.